The controlling of paleo-riverbed migration on Arsenic mobilization in groundwater in the Red River Delta, Vietnam - Trung, Dang Tran; Nhan, Nguyen Thi; Don, Than Van; Hung, Nguyen Kim; Kazmierczak, Jolanta; Nhan, Pham Quy (Vietnam Journal of Earth Sciences, 2020)
In the Red River Delta, the concentrations of Arsenic in groundwater of alluvial dominated systems are very high, exceeding the WHO’s permissible. The correlation between the Arsenic concentrations in groundwater and the age of Holocene sediment as a key controlling groundwater Arsenic concentration in the Red River delta has been investigated. The evolution of sediments in the Holocene is closely related to paleo-riverbed migration in the past. A combination of methods is implemented including remote sensing, multi-electrode profiling (MEP), gamma-logging, drilling, soil sample and groundwater modeling. The resul has identified the shape, sediment compositions and location of the six paleo-riverbed periods. The age of the paleo-riverbed is determined by drilling, soil sampling and optically stimulated luminescence (OSL) in the laboratory. The oldest sediments is 5.9±0.4 ka BP in Phung Thuong near the mountain, the youngest one is from 0.4÷0.6 ka BP in H-transect near the Red River and the rest of the other is around 3.5 ka BP. The modeling results by using MODFLOW and MT3D show that the dynamics of paleo-riverbeds controlling Arsenic mobilization in groundwater in the Red River Delta. When the river moved to another position, the current river position at that time was filled with younger sediments and became paleo-riverbed formation with reducing conditions, Arsenic content which was adsorbed in the previous stage then released into groundwater. Therefore, Arsenic concentration in groundwater of young Holocene sediments is higher than in older ones which elucidates that paleo-riverbed migration controls on Arsenic mobilization in groundwater in the study area.